To solve the equation \(-\frac{3}{5}x = \frac{2}{5}\) using inverse operations, we need to isolate \(x\).
-
Start with the equation: \[ -\frac{3}{5}x = \frac{2}{5} \]
-
To isolate \(x\), we can multiply both sides by the reciprocal of \(-\frac{3}{5}\), which is \(-\frac{5}{3}\): \[ x = \frac{2}{5} \cdot -\frac{5}{3} \]
-
Perform the multiplication: \[ x = -\frac{2 \cdot 5}{5 \cdot 3} = -\frac{10}{15} \]
-
Simplify \(-\frac{10}{15}\): \[ x = -\frac{2}{3} \]
So the solution is: \[ x = -\frac{2}{3} \]
Thus, the correct answer is D (-2/3).